Comparative Study of Different Classification Methods and Winner Takes All Approach - Abdel Aziz, Khaled Mahmoud; Elsonbaty, Loutfia (Salehan Institute of Higher Education, 2024)
One of the most popular methods in remote sensing for gathering and evaluating satellite data is the classification of images. Several categories exist for image classification techniques, including supervised and unsupervised classification, pixel-based, object-based, and rule-based approaches. Each type of technique has pros and cons of its own. Choosing the method that produces the best results is one of the issues with image classification. The